Carotid Geometry and Wall Shear Stress Independently Predict Increased Wall Thickness—A Longitudinal 3D MRI Study in High-Risk Patients - Strecker, Christoph; Krafft, Axel Joachim; Kaufhold, Lilli; Hüllebrandt, Markus; Treppner, Martin; Ludwig, Ute; Köber, Göran; Hennemuth, Anja; Hennig, Jürgen; Harloff, Andreas (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Carotid geometry and wall shear stress (WSS) have been proposed as independent risk factors for the progression of carotid atherosclerosis, but this has not yet been demonstrated in larger longitudinal studies. Therefore, we investigated the impact of these biomarkers on carotid wall thickness in patients with high cardiovascular risk. Methods: 97 consecutive patients with hypertension, at least one additional cardiovascular risk factor and internal carotid artery (ICA) plaques (wall thickness ≥1.5mm and degree of stenosis ≤50%) were prospectively included. They underwent high-resolution 3D multi-contrast and 4D flow MRI at 3 Tesla both at baseline and follow-up. Geometry (ICA/common carotid artery (CCA)-diameter ratio, bifurcation angle, tortuosity and wall thickness) and hemodynamics (WSS, oscillatory shear index (OSI)) of both carotid bifurcations were measured at baseline. Their predictive value for changes of wall thickness 12 months later was calculated using linear regression analysis for the entire study cohort (group 1, 97 patients) and after excluding patients with ICA stenosis ≥10% to rule out relevant inward remodeling (group 2, 61 patients). Results: In group 1, only tortuosity at baseline was independently associated with carotid wall thickness at follow-up (regression coefficient =-0.52, p<0.001). However, after excluding patients with ICA stenosis ≥10% in group 2, both ICA/CCA-ratio (0.49, p<0.001), bifurcation angle (0.04, p=0.001), tortuosity (-0.30, p=0.040), and WSS (-0.03, p=0.010) at baseline were independently associated with changes of carotid wall thickness at follow-up. Conclusions: A large ICA bulb and bifurcation angle and low WSS seem to be independent risk factors for the progression of carotid atherosclerosis in the absence of ICA stenosis. By contrast, a high carotid tortuosity seems to be protective both in patients without and with ICA stenosis. These biomarkers may be helpful for the identification of patients who are at particular risk of wall thickness progression and who may benefit from intensified monitoring and treatment.